2019
DOI: 10.1038/s41467-019-11678-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative use of renin-angiotensin system inhibitors and outcomes in patients undergoing cardiac surgery

Abstract: It remains disputable about perioperative use of renin-angiotensin system inhibitors (RASi) and their outcome effects. This multicenter retrospective cohort study examines association between use of perioperative RASi and outcomes in patients undergoing coronary artery bypass graft and/or valve surgery. After the exclusion, the patients are divided into 2 groups with or without preoperative RASi (PreRASi, n = 8581), or 2 groups with or without postoperative RASi (PostRASi, n = 8130). With using of propensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This protective effect is in line with our previously findings in the entire patient sample, without controlling for whether the patient has HF or not. 32 Comparing the results of the survival analyses between these two studies, we found smaller hazard ratios for the protective effect of PreRASi on postoperative mortality. This implies that PreRASi exerts more significant protection against mortality in patients with HF, which was further supported by the findings that neither PreRASi nor PostRASi provided protection against 6-year mortality in patients without HF history (Figure S8, http://links.lww.com/SLA/D700, S9, http://links.lww.com/SLA/D701).…”
Section: Discussionmentioning
confidence: 76%
“…This protective effect is in line with our previously findings in the entire patient sample, without controlling for whether the patient has HF or not. 32 Comparing the results of the survival analyses between these two studies, we found smaller hazard ratios for the protective effect of PreRASi on postoperative mortality. This implies that PreRASi exerts more significant protection against mortality in patients with HF, which was further supported by the findings that neither PreRASi nor PostRASi provided protection against 6-year mortality in patients without HF history (Figure S8, http://links.lww.com/SLA/D700, S9, http://links.lww.com/SLA/D701).…”
Section: Discussionmentioning
confidence: 76%
“…Our study focused only on the effects of antihypertensive medication on postoperative mortality and functional decline during the acute phase of hospitalization following major surgeries. A previous multicenter retrospective cohort study showed that the postoperative initiation of RASis even at discharge was associated with reduced long-term mortality rate in patients undergoing cardiac surgery [39]. Randomized controlled trials are needed to determine whether perioperative RASi initiation could improve outcomes following cardiac and non-cardiac surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, RAS blockade is still not recommended before cardiovascular surgery. Current randomized trials are underway to appropriately assess the pre-operative use of RAS blockade in patients undergoing heart surgery [ 31 ].…”
Section: Discussionmentioning
confidence: 99%